Diachronic transformations in Troubles fiction: a study in models and methods - Rafferty, Pauline (2008)
This dissertation examines relationships between Northern Irish Troubles fiction and its secondary critical literature. Producers of genre are viewed as consumers of the genre to which they contribute and the consumption of genre is seen as a pre-requisite of production. The research method is designed to examine genre systematically through the analysis of a large data set representative of the genre spectrum. It employs analytical concepts drawn from semiotics, specifically, paradigms and syntagms. Results are interpreted using Raymond Williams' "structures of feeling" and a modified version of Stuart Hall's encoding/decoding model.